EVIDENCE OF THE ASSOCIATION BETWEEN SLEEP DURATION AND BLOOD PRESSURE IN ADOLESCENTS: A SYSTEMATIC REVIEW - Santos,Emanuela de Souza Gomes dos (2021)
ABSTRACT Objective: To review the epidemiological evidence of the association between sleep duration and blood pressure in adolescents. Data sources: We performed a systematic review of observational studies in Medline, Scopus, Lilacs, Web of Science, Science Direct databases and Virtual Libraries in English, Spanish and Portuguese published until September 2018. Studies were selected first by title and abstract, then by complete reading, according to the eligibility criteria. The reference list of selected articles was evaluated in order to retrieve relevant studies. Data synthesis: Initially, 1,455 articles were retrieved. After exclusion due to duplicity or not meeting the eligibility criteria, 13 articles were included in the review. Studies varied greatly in sample size (143 to 6,940 patients), methods of measuring blood pressure and sleep duration, cutoff points, categorization and adjustment of variables. The main evidence from the studies is that short sleep duration is associated with high blood pressure in adolescence, although the presence of association between high blood pressure and long sleep duration is possible, but not clear in the literature. Conclusions: Sleep duration, especially short duration, is associated with high blood pressure in adolescents. Such evidence draws attention to implications on cardiovascular health in this age group.